2017
DOI: 10.1039/c7tc02459b
|View full text |Cite
|
Sign up to set email alerts
|

Optimized electron-transport material based on m-terphenyl-diphenylphosphine oxide with the harmonious compatibility of high ET and electron mobility for highly efficient OLEDs

Abstract: Harmonious compatibility of high ET and electron mobility for highly efficient OLEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…The m e values of TPBi are also in line with those in the literature. 55 We consider that BBIA is a good ETM due to its high thermal stability and high electron mobility. The LED devices were fabricated using colloidal perovskite nanocrystals as the emission layer (EML).…”
Section: Resultsmentioning
confidence: 99%
“…The m e values of TPBi are also in line with those in the literature. 55 We consider that BBIA is a good ETM due to its high thermal stability and high electron mobility. The LED devices were fabricated using colloidal perovskite nanocrystals as the emission layer (EML).…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 2 shows the simulated mobility vs. experimental data from Zhang, et al (2). For the simulation based on the accurate energy model (orange) we find a very good match to experimental data and the Gaussian disorder model (blue) underestimating the mobility by a factor of four while reproducing the experimental trend.…”
Section: Resultsmentioning
confidence: 66%
“…The HTL of PVK in the LEDs device structure plays an important role, so the 5% NaBr‐modified CsPbBr 3 NPs LED device with different thickness of PVK are fabricated to explore it (Figure S14, Supporting Information). It is found that the performance is the worst without PVK because of the exciton quenching of CsPbBr 3 NPs by NiO x and charge imbalance from that low electron mobility of TPBi miss match with high hole mobility of NiO x , and it gets better and then gets worse with the increase of PVK thickness. When the PVK film is spin coated from 8 mg mL −1 chlorobenzene (CB) solution, the LEDs device possesses the best performance.…”
Section: Resultsmentioning
confidence: 99%